2017
DOI: 10.1002/jso.24796
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between preoperative breast MRI and surgical treatment of non‐metastatic breast cancer

Abstract: Background and Objectives More extensive surgical treatments for early stage breast cancer are increasing. The patterns of preoperative MRI overall and by stage for this trend has not been well established. Methods Using Breast Cancer Surveillance Consortium registry data from 2010 through 2014, we identified women with an incident non-metastatic breast cancer and determined use of preoperative MRI and initial surgical treatment (mastectomy, with or without contralateral prophylactic mastectomy (CPM), recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…2a ) ( low certainty ) [ 19 , 21 ]. In 11 observational studies [ 11 , 12 , 22 24 , 27 , 32 36 ], the odds of BCS was lower but the evidence was very uncertain (OR 0.49; 95% CI 0.29 to 0.82) and only two cohort studies reported adjusted OR showing similar results ( very low certainty ) [ 32 , 35 ] (Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2a ) ( low certainty ) [ 19 , 21 ]. In 11 observational studies [ 11 , 12 , 22 24 , 27 , 32 36 ], the odds of BCS was lower but the evidence was very uncertain (OR 0.49; 95% CI 0.29 to 0.82) and only two cohort studies reported adjusted OR showing similar results ( very low certainty ) [ 32 , 35 ] (Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the definitions for positive margins across studies were heterogenous (i.e. < 1 mm [ 11 , 27 ] or < 5 mm [ 29 ]) or not clearly described [ 36 ], even among the included centres of the only RCT reporting this outcome [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found similar nationwide surgical trends among the population of patients receiving NAC. As in the non-NAC setting, the decision to pursue bilateral mastectomy for unilateral breast cancers after NAC is multifactorial and likely influenced by patient, physician and treatment factors, such as increased use of magnetic resonance imaging, 27,28 increased genetic testing and identification of high-risk patients who benefit from bilateral mastectomy, 29 surgeon's preference 30 and patient preference due to fear of additional therapies, recurrence or anticipated regret [31][32][33][34] or desire for cosmetic symmetry and increased access to reconstruction. 35 In our study, we observed that the receipt of bilateral mastectomy is more common among younger patients from a more advantaged sociodemographic background even though these characteristics were associated with attainment of pCR.…”
Section: Discussionmentioning
confidence: 99%